2021
DOI: 10.1161/circimaging.120.011774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Adenosine Stress T1 Mapping

Abstract: Background: Adenosine stress T1 mapping is an emerging magnetic resonance imaging method to investigate coronary vascular function and myocardial ischemia without application of a contrast agent. Using gene-modified mice and 2 vasodilators, we elucidated and compared the mechanisms of adenosine myocardial perfusion imaging and adenosine T1 mapping. Methods: Wild-type (WT), A 2A AR −/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Although the exact mechanisms behind the ΔT1 response are not fully understood, it is largely mediated by endothelium-dependent mechanisms, while myocardial perfusion reserve is endothelium independent. 4 Our findings support the hypothesis that cardiac endothelial injury may underlie vascular impairment in PACS+POTS. It is recognized as a limitation in the current study that a POTS group without prior COVID-19 was not included.…”
supporting
confidence: 86%
“…Although the exact mechanisms behind the ΔT1 response are not fully understood, it is largely mediated by endothelium-dependent mechanisms, while myocardial perfusion reserve is endothelium independent. 4 Our findings support the hypothesis that cardiac endothelial injury may underlie vascular impairment in PACS+POTS. It is recognized as a limitation in the current study that a POTS group without prior COVID-19 was not included.…”
supporting
confidence: 86%
“…This likely reflects the timings of the first-pass perfusion acquisitions, which were not performed at peak stress in this study (i.e. acquired at 4 min and 15 min vs. typically 1–2 min in clinical practice) rather than the choice of vasodilator agent, given recent animal studies have shown no significant differences in MBF when comparing adenosine and regadenoson 40 . Our data supports that there are clear differences in stress T1 reactivity between the methods tested, with ShMOLLI demonstrating a significantly greater stress T1 response and effect size.…”
Section: Discussionmentioning
confidence: 98%
“…This may also account for the continued trends of systemic measurements (BP, HR, RPP) through the 4× adenosine dose, as each organ has differing ratios of each receptor 56 . Additionally, the continued increase in MBV after MBF begins to drop can be explained by the recent findings of Shah et al, who found that adenosine‐induced changes in MBF and MBV are controlled by different adenosine receptors: MBF via the A 2A adenosine receptor, and MBV through both the A 2A and A 2B receptor subtypes 57 . We should also point out that, since the distribution of each adenosine receptor subtype varies from species to species, 56 it is possible that our model may need to be adjusted for stress imaging studies in other species.…”
Section: Discussionmentioning
confidence: 99%